Walking a tightrope: a scoping review of the use, perceptions and experiences of harm reduction strategies in self-harm management - Nina Veetnisha Gunnarsson; Cecilia Moberg (Discover Mental Health)
Abstract Harm reduction involves safer practices for self-harm, a concept well-established in drug management but less explored in the context of self-harm. This scoping study examines empirical research on harm reduction strategies in self-harm management, focusing on practitioners' and individuals' perspectives. The scoping review follows the Joanna Briggs Institute (JBI) recommendations and analyses internationally peer-reviewed empirical studies. Systematic searches in databases like CINAHL, Scopus, Sociological Abstracts, PsycINFO, and PubMed identified 377 studies, with seven meeting the inclusion criteria. Originating from the UK and focused on the nursing field, recent publications highlighted substitution strategies and alternatives to existing self-harm behaviours, such as snapping an elastic band on the wrist. Both practitioners and those who self-harm used and recommended substitution strategies, but these were also viewed as a form of self-harm. One social scientific study revealed a preference for harm reduction among self-harming individuals, advocating its use to counter oppressive practices. The study metaphorically illustrates practitioners navigating a delicate balance, akin to “walking a tightrope,” striving to prevent harm while recognizing that individuals at times needs to harm themselves in specific situations. The review's emphasis on harm reduction in clinical settings suggests a narrower focus, prompting a call for broader research to understand autonomy and the dynamics of harm reduction in diverse contexts related to self-harm decision-making.